Fluoride triggers lysis in Streptococcus mutans by inhibition of the Clp protease complex, leading to an unabated competence cascade - Aditya Banerjee; Sophie Pickelner; Faith Smith; Livia M. A. Tenuta; Randy B. Stockbridge (Proceedings of the National Academy of Sciences, 2025)
Fluoride has long been known to possess antimicrobial properties. For many bacteria, the toxic effects of fluoride are reversible. However, fluoride has also been shown to trigger lysis and cell death in many other diverse bacterial species, including dental pathogens. The underlying molecular mechanisms responsible for fluoride-induced cell lysis have not been established. Using Streptococcus mutans as a model, we show that fluoride elicits an uncontrolled stress response characterized by upregulation of competence pathways and extensive cell wall degradation. While controlled and limited autolysis under stress is an adaptive response, we show that expression of the competence-associated alternative sigma factor ComX is prolonged under fluoride stress, relative to other stressors. Using in vitro and in vivo analyses, we show that fluoride disrupts the typical tight temporal control of ComX by specifically inhibiting assembly and activity of Clp ATPases responsible for its proteolytic degradation. Unchecked, ComX upregulates bacteriocins and autolysins, while simultaneously suppressing immunity peptide expression via a 6S RNA-mediated mechanism. Thus, fluoride subverts cellular mechanisms to turn off competence pathways that are induced under cellular stress, causing irreversible damage to the cell wall and ultimately cell death. Phenylalanine partially restores Clp protease assembly and activity, providing a rationale for the frequent presence of a gene encoding chorismate mutase in fluoride-responsive operons. Together, our findings reveal the molecular mechanism of fluoride-dependent lysis in bacteria, fifty years after this phenomenon was first reported. These pathways could be exploited to potentiate the antimicrobial effects of oral fluoride.